School mediation: at the media superior level (Revista de Investigaciones Universidad del Quindío, 2021)
The national educational system in Mexico includes basic education, upper secondary education and higher education. The subject of interest in this document is the importance of school mediation in the upper secondary level known as baccalaureate or preparatory, this level prepares and trains young students for admission to higher or university education. In this tenor of training students, it is pertinent to socialize the tools and techniques of alternative mechanisms for the management and resolution of conflicts in favour of a culture of peace. School mediation helps the educational system in the formation of the student since he is a person who is transitioning to an adult age in which he acquires a greater number of responsibilities. This type of mediation allows the student community to enhance the spaces for coexistence, reinforcing dialogue and communication with active, plural participation and respect.
Keywords: conflict; culture of peace; education; alternative mechanisms; violence